2022
DOI: 10.3390/su142114259
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Apparent and Intellectual Sustainability Independence on the Credibility Gap of the Accounting Information

Abstract: This study aims to recognize the sustainability independence of the Jordanian Association of Certified Public Accountants (JACPA/JCPA) and its impact on the credibility gap of the accounting information of companies operating in Jordan. This study demonstrates the effects of the apparent and intellectual sustainability independence on the credibility gap of accounting information. A total of 93 online questionnaires were analyzed using multiple regressions. The results revealed an impact of the apparent indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Notably, intelligence models have been revamped to correspond to the web dimension and the strategic outlook (Lanzolla and Giudici 2017 ). Meanwhile, models and tools of information management have evolved, in line with the new requirements of strategic decision, and the evolution of these models and tools resulted from the identification of the key analysis dimensions (Hamdallah et al 2022 ; Kuosa 2011 ; Reinmoeller and Ansari 2016 ; Garzella and Fiorentino 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, intelligence models have been revamped to correspond to the web dimension and the strategic outlook (Lanzolla and Giudici 2017 ). Meanwhile, models and tools of information management have evolved, in line with the new requirements of strategic decision, and the evolution of these models and tools resulted from the identification of the key analysis dimensions (Hamdallah et al 2022 ; Kuosa 2011 ; Reinmoeller and Ansari 2016 ; Garzella and Fiorentino 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Integrated Reporting Council has taken a proactive step in aligning sustainability reporting standards by coordinating standards for climate-related disclosures (Rowbottom, 2023). Hamdallah, Al-N'eimat, et al (2022) and Sáez-Martínez et al (2016) emphasize that sustainability reporting not only measures a company's activities, but also serves as a means of accountability to both internal and external stakeholders, with the ultimate goal of promoting sustainable evolution. Bartlett (2012) points out that the terms "sustainability" and "sustainable" are differently depending on who is using them and their distinct connotations.…”
Section: Sp Reportingmentioning
confidence: 99%
“…HRM practices represent the development of human resource skills through the selection, training, and increase of workforce motivation through incentives and compensation, which ultimately leads to enhancing human resource competencies to achieve managerial creativity (Taamneh et al, 2022;Casio, 2013). Abu Zaid (2014) and El-Sherbiny (2016) confirmed that human resource management and its practice provide a distinct way to increase administrative creativity within organizations, in addition to being an attraction system for employees and an essential element in the process of developing, motivating, and maintaining them; ultimately this is the main factor that contributes to the achievement and sustainability of an organization's goals (Hamdallah et al, 2022). The process of change, turning certain inventive ideas into a service, commodity, product, or benefit with value for the user or customer is known as administrative creativity (Al-Okaily et al, 2021).…”
Section: Introductionmentioning
confidence: 99%